Governing Muslims and Islam in contemporary Germany : race, time, and the German Islam Conference - Hernandez Aguilar, Luis Manuel. (Muslim Minorities, 2018)
In 2006 against the background of the increasing problematization of Muslims and Islam in German public debate, the German government established the German Islam Conference. In a post 9/11 world, this was a time period shaped by the global war on terror, changes in the German naturalization law, the proliferation of racism targeting Muslims, and the expansion of security apparatuses. In Governing Muslims and Islam in Contemporary Germany Luis Manuel Hernández Aguilar critically analyzes the institutionalization of the Conference and the different projects this institution has set in motion to govern Islam and Muslims against the looming presence of racial representations of Muslims. The analysis begins with the foundation of the Conference until the end of its second phase in 2014.